The drop in female homicide victimisation in Australia - Forrest, Walter (Journal of criminology, 2022)
Despite widespread community concern about the incidence of lethal violence against women in Australia, the numbers and rates of women murdered each year have been falling for almost 30 years. The risk of homicide victimisation among Australian women is now the lowest it has ever been since federation. Few studies have explored these patterns or sought to explain their development. One plausible explanation, anticipated by feminist theories of violence, is that homicide has declined as the status of women and gender equality have increased. In this paper, I analyse changes in the annual female homicide victimisation rate in Australia from 1962 to 2016. Using unobserved components models, I investigate the extent to which increases in either the status of women or gender equality can account for the decline in female homicide victimisation since the late 1980s. Despite absolute and relative advances in women's educational access and achievement, labour force participation, and earnings, those changes had little discernible impact on the aggregate-level risk of lethal violence against women. Instead, other social and economic conditions, such as falling unemployment, the shrinking of the young male population and ongoing urbanisation, seem better able to explain recent improvements in women's safety.